PILOTS’ ERRORS ACCOUNTING AND CONTROL IN THE PROCESS OF AIRCRAFT FLIGHT OPERATION AS A SIMULATOR TRAINING TASK - Задкова, Е. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
This article analyzes the flight data processing systems in order to determine the possibility of automated control and accounting of errors made by the pilots in the process of aircraft flight operation during the initial simulator training of flight personnel. The paper presents a classification and brief description of the training devices used in the practice of pilot training. It is proposed to use the program, which is flight data container, which helps the instructor to put in perspective and analyze the performance of simulator flight missions by the cadet-pilots